Utilization of whey powder as substrate for low-cost preparation of β-galactosidase as main product, and ethanol as by-product, by a litre-scale integrated process. (December 2017) - You, Shengping; Chang, Hongxing; Yin, Qingdian; Qi, Wei; Wang, Mengfan; Su, Rongxin; He, Zhimin
Graphical abstract: Highlights: Whey powder was used for high-production of β-galactosidase by an integrated process. The integrated process was developed successfully in a litre scale. An up-dated mathematic model for the recycling permeabilization was established. β-Galactosidase product was 5.15 U/mg and by-product ethanol was 31.08% (v/v). Abstract: Whey powder, a by-product of dairy industry, is an attractive raw material for value-added products. In this study, utilization of whey powder as substrate for low-cost preparation of β-galactosidase as main product and ethanol as by-product were investigated by a litre-scale integrated strategy, encompassing fermentation, isolation, permeabilization and spray drying. Firstly, through development of low-cost industrial culture and fed-batch strategies by Kluyveromyces lactis, 119.30 U/mL β-galactosidase activity and 16.96 mg/mL by-product ethanol were achieved. Afterward, an up-dated mathematic model for the recycling permeabilization was established successfully and 30.4 g cells sediment isolated from 5 L fermentation broth were permeabilized completely by distilled ethanol from broth supernatant. Then β-galactosidase product with 5.15 U/mg from protection of gum acacia by spray drying was obtained. Furthermore, by-product ethanol with 31.08% (v/v) was achieved after permeabilization. Therefore, the integrated strategy using whey powder as substrate is a feasible candidate for industrial-scale implementation.